VD_FINDINFO Décision / 2012 / 673 vom 15. Juni 2012 - VD Tribunal cantonal (2012)
RISQUE DE COLLUSION, DÉTENTION PRÉVENTIVE | 221 al. 1 let. b CPP (CH), 222 CPP (CH), 228 CPP (CH), 393 al. 1 let. b CPP (CH)